High antibiotic resistance of Helicobacter pylori and its effect on tailored and empiric eradication of the organism in Lower Silesia, Poland. Issue 2 (23rd November 2016) - Ferenc, Stanisław; Gnus, Jan; Kościelna, Magdalena; Kinda, Małgorzata; Yarka, Andriy; Stewart, Luke; Witkiewicz, Wojciech
Abstract: Background: At present, the resistance to antibiotics is considered the most important reason for Helicobacter pylori (HP) eradication failure. The aim of this study was to estimate the prevalence of antimicrobial resistance of HP strains and to evaluate tailored and empiric therapeutic regimens in patients with peptic ulcer disease associated with infection of this microorganism. Materials and Methods: Between May 2011 and February 2013, 185 consecutive Polish patients with at least one positive Helicobacter pylori test (urease test, histopathologic examination, and/or culture) underwent eradication therapy. Those with positive culture were prescribed a tailored triple regimen, whereas those with no culture available received an empiric quadruple concomitant regimen or levofloxacin—containing triple therapy. Results: There were no HP strains resistant to amoxicillin; however, 56.7% were resistant to metronidazole, 55.2% to clarithromycin, and 5.9% to levofloxacin. Dual resistance was detected in 32.8% of individuals. Tailored and empiric therapies achieve cure rates, respectively, 95.5% and 86.6% by intention‐to‐treat and 95.5% and 91.3% by per‐protocol analysis ( P  > 0.05). Conclusions: Antibiotic resistance is notably high in Poland currently, but both tailored and empiric therapies can achieve acceptable cure rates equal to or higher than 90%.